Jati Kasilih Ku Janti In The Seren Tahun Ceremony: Ritual Communication And Cultural Meaning - Muslim Muslim; Muhammad Reza; Ratih Siti Aminah; Jordy Satria Widodo; Yuyus Rustandi; Andi Chairunnas (UNIVERSITAS PAKUAN, 2025)
Abstract. This study examines how the Sundanese philosophical principle Jati Kasilih ku Janti is manifested and communicated through the Seren Tahun ceremony at Kampung Budaya Lembur Anyar, Bogor Regency. The research aims to: (1) describe the communicative architecture of the ceremony using the SPEAKING framework; (2) analyze how the philosophy is encoded in ritual speech genres and semiotic object systems; and (3) construct a Ritual Communication Model grounded in the ceremony findings. A qualitative design integrating ethnography of communication and semiotic analysis was employed, with data from observational fieldwork across three consecutive ceremony cycles (2022–2024), in-depth interviews with 19 informants, and semiotic analysis of 28 ritual symbols. Six ritual speech genres and four categories of symbolic objects were identified as primary philosophical encoding mechanisms. The proposed Ritual Communication Model (RCM-JKJ) integrates textual, symbolic, performative, and witness communication layers within a condensation-iteration-differentiated reception dynamic. This model contributes a locally grounded theoretical framework to ritual communication scholarship and advances the de-Westernization of organizational communication theory in Indonesia.